Pathogenic mechanism of second hand smoke induced inflammation and COPD - Birru, Rahel; Di, Y. Peter (Frontiers in Physiology, 2012)
Second hand smoke (SHS) introduces thousands of toxic chemicals into the lung, including carcinogens and oxidants, which cause direct airway epithelium tissue destruction. It can also illicit indirect damage through its effect on signaling pathways related to tissue cell repair and by the abnormal induction of inflammation into the lung. After repeated exposure to second hand smoke, these symptoms can lead to the development of pulmonary inflammatory disorders, including chronic obstructive pulmonary disease (COPD). COPD is a severe pulmonary disease characterized by chronic inflammation and irreversible tissue destruction. There is no causal cure, as the mechanism behind the development and progression of the disease is still unknown. Recent discoveries implicate genetic predisposition associated with inflammatory response contributed to the development of COPD, linked to irregular innate and adaptive immunity, as well as a risk factor for cancer. The use of animal models for both cigarette smoke (CS) and SHS associated in vivo experiments has been crucial in elucidating the pathogenic mechanisms and genetic components involved in inflammation related development of COPD.